An Emerging Multi-mechanism and Multi-modal Approach in Interventional Glaucoma Therapy - J. Morgan Micheletti; Mitchell Shultz; Inder Paul Singh; Thomas W. Samuelson (Ophthalmology and Therapy)
Abstract The glaucoma treatment paradigm is in evolution. The topical medications-first approach is limited by significant barriers such as high rates of nonadherence and side effects including ocular surface disease. The era of interventional glaucoma has seen the development of selective laser trabeculoplasty (SLT), procedural pharmaceuticals, and minimally invasive glaucoma surgeries (MIGS). New and emerging data support the use of these interventional treatment modalities early in the course of glaucoma rather than reserving them for advanced or treatment-recalcitrant cases. The various treatments available represent multiple mechanisms (e.g., trabecular outflow, uveoscleral outflow, aqueous suppression) and modalities (medications, laser, incisional surgery) by which intraocular pressure (IOP) is reduced. Many patients require more than one treatment to achieve adequate IOP reduction and glaucoma control. Comprehensive IOP control—reduction of both mean IOP and IOP fluctuation—can best be achieved by targeting multiple mechanisms of IOP reduction and taking advantage of the attributes of multiple treatment modalities.